PEMBERDAYAAN MASYARAKAT DALAM DETEKSI DINI KANKER LEHER RAHIM DI DESA KERTASARI RENGASDENGKLOK KABUPATEN KARAWANG - A. Achmad Fariji; Herry Sugiri; Mardianti Mardianti (Poltekkes Kemenkes Bandung, 2022)
The VIA examination is a screening examination for cervical cancer using 3-5% acetic acid on the inspector and can be seen by direct observation, this method is done to see the color changes that occur after smearing, this color change can be directly observed after 1-2 minutes after application with the naked eye. The procedure for carrying out the IVA test is quite simple so that this examination can be carried out by health workers other than gynecologists. The purpose of the VIA examination is to reduce morbidity or mortality from the disease with early treatment of cases found and to determine abnormalities that occur in the cervix. Participants in this community service are married mothers and have had sexual relations, women of childbearing age who are in the working area of the Rengasdengklok Health Center. In implementing this community service, our community service team first conducted observations and preliminary studies in order to obtain information and data, then we conducted socialization related to early detection of cervical cancer with VIA examination. The result of this community service activity is that participants can understand the material presented and are willing to carry out an IVA test for early prevention of cervical cancer.